'Day number': A promoter routine of flexibility and conceptual understanding - Serrazina, Maria de Lurdes (2017)
This article reports part of the research developed by a Project focused on flexible calculation. In this article, we discuss different perspectives of flexibility and adaptive thinking in literature. We also discuss the idea of proceptual thinking and how this idea is important in our perspective of adaptive thinking. The article analyzes a situation named 'Day number' developed by a first grade classroom and its teacher. It is a daily activity at the beginning of the school day. It consists of looking for the date number and thinking about different ways of writing it using the four arithmetic operations. The analyzed activity occurred on March 19, so the challenge was to write the number 19 in several ways. The data show the students’ enthusiasm and their efforts to find different ways of writing the number. Some used large numbers and division, which they were just starting to learn. The students presented symbolic expressions of 19, decomposing and recomposing it in a flexible manner.